Smallholders' commercialization through cooperatives: A diagnostic for Ethiopia - Bernard, Tanguy; Gabre-Madhin, Eleni Zaude; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2007)
This paper examines the impact of cooperatives on smallholder commercialization of cereals, using detailed household data from rural Ethiopia. We review the involvement of cooperatives, in terms of who participates and where they are located. We then use the strong government role in promoting the establishment of cooperatives to assume that the decision of where to establish a cooperative is largely driven by external considerations, and is thus exogenous to the members themselves justifying the use of propensity-score matching in order to compare households that are cooperative members to similar households in comparable areas without cooperatives. Four conclusions are derived from the analysis. First, despite the spread of cooperatives – they existed in less than 15 percent of districts in 1994 and nearly 35 percent in 2005 – there are important disparities across regions. Within regions, cooperatives tend to be located in areas that already have better access to markets and lower exposure to price and environmental risks. Second, at the household level participation is only 9 percent, with poorer households less likely to participate. Third, while cooperatives obtain higher prices for their members, they are not associated with a significant increase in the overall share of cereal production sold by their members. Fourth, these average results hide considerable heterogeneity in the impact across households. In particular, we find smaller farmers tend to reduce their marketable surplus as a result of higher prices, while the opposite is true for larger farmers.